For out of Babylonia shall come Torah and the word of the Lord from Nehar Peqod : the quest for Babylonian tannaitic traditions - Cohen, Barak S. (The Brill Reference Library of Judaism, 2017)
In For Out of Babylonia Shall Come Torah and the Word of the Lord from Nehar Peqod , Barak S. Cohen reevaluates the evidence in Tannaitic and Amoraic literature of an independent "Babylonian Mishnah" which originated in the proto-talmudic period. The book focuses on an analysis of the most notable halakhic corpora that have been identified by scholars as originating in the Tannaitic period or at the outset of the amoraic. If indeed such an early corpus did exist, what are its characteristics and what, if any, connection does it have with the parallel Palestinian collections? Was this Babylonian Mishnah created in order to harmonize the Palestinian Mishnah with a corpus of rabbinic teachings already existent in Babylonia? Was this corpus one of the main contributors to the forced interpretations and resolutions found so frequently in the Bavli?